Short-Term Application of Polymer-Coated Mono-Ammonium Phosphate in a Calcareous Soil Affects the Pools of Available Phosphorus and the Growth of Hypericum × moserianum (L.) - Pizzeghello, Diego; Schiavon, Michela; Maretto, Laura; Stevanato, Piergiorgio; Ertani, Andrea; Altissimo, Adriano; Nardi, Serenella (Frontiers in Sustainable Food Systems, 2019)
Mineral phosphorus (P) fertilization in calcareous soils is not efficient enough to ensure optimal plant growth. Therefore, a higher P input is generally needed. Polymer-coated fertilizers are a promising fertilizer category that seems to affect soil extractable P, thus permitting a reduction in fertilizer rates. We tested this hypothesis in a short-term (45 days) field trial by evaluating both the agronomic and the environmental implications. In this study, two conventional fertilizers (single superphosphate, SSP; mono-ammonium phosphate, MAP) and a slow P-release fertilizer (polymer-coated MAP, PCMAP) were tested for their effects on soil P pools by combining different P rates and degrees of coating. The P soil test was determined with either Olsen or Mehlich-3 solution (available P), whereas the P soil release was estimated through water extraction. The efficiency of fertilizers was evaluated by assessing the growth of Hypericum × moserianum (L.) plants. As expected, both SSP and MAP influenced the soil Mehlich-3-P, Olsen-P, and water-P, as concentrations increased with the fertilizer rate. Conversely, PCMAP decreased the soil extractable P with increasing coating. The plant dry weight and P uptake linearly correlated with the fertilizer rate for SSP and MAP, whilst they achieved the maximum yield with PCMAP. This result indicates the underdosing for conventional fertilizers. With reference to the soil test P with water-P, the presence of change points showed low water-P release concentrations for PCMAP and SSP, and high water-P release for MAP. In conclusion, in the short-term period both soil extractable P and water-P depend on the type of fertilizer, whereas the amount of added P has rather a secondary role. PCMAP, in particular, ensures high plant P use efficiency with minimum environmental impacts.